2020
DOI: 10.3390/cancers12051172
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Angiogenesis, a Key Step in Cancer Vascularization, and Treatment Approaches

Abstract: Angiogenesis is a term that describes the formation of new blood and lymphatic vessels from a pre-existing vasculature. This allows tumour cells to acquire sustenance in the form of nutrients and oxygen and the ability to evacuate metabolic waste. As one of the hallmarks of cancer, angiogenesis has been studied extensively in animal and human models to enable better understanding of cancer biology and the development of new anti-cancer treatments. Angiogenesis plays a crucial role in the process of tumour gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 115 publications
1
74
0
1
Order By: Relevance
“…These findings suggested that STAT-3 might be a promising therapeutic target for cancer treatment with few side effects. The vascular endothelial growth factor (VEGF), originally known as the vascular permeability factor (VPF), is a signal protein that can stimulate the formation of blood vessels in cancer development [42]. Sim et al showed that STAT-3 could regulate the expression of VEGF in various types of cancers [43].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that STAT-3 might be a promising therapeutic target for cancer treatment with few side effects. The vascular endothelial growth factor (VEGF), originally known as the vascular permeability factor (VPF), is a signal protein that can stimulate the formation of blood vessels in cancer development [42]. Sim et al showed that STAT-3 could regulate the expression of VEGF in various types of cancers [43].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A and VEGFRs are well-characterized targets for antiangiogenic therapeutics and these drugs have shown a varying range of effectiveness across tumor types [272]. Monoclonal antibodies such as Bevacizumab (Avastin), a humanized monoclonal antibody that blocks VEGF-A, or small molecules such as vandetanib, which inhibits tyrosine kinases downstream of VEGF, are examples of anti-VEGF treatment.…”
Section: Therapeutic Targets Regulated By Tgli1mentioning
confidence: 99%
“…Angiogenesis is an essential process in tumor development and metastatic spread, as it constantly supplies tumor mass with oxygen and nutrients [ 101 ]. In this context, several reports have provided evidence that the endothelial cells of the surrounding tumor stroma express FGFRs that mediate the stimulatory action of FGFs [ 102 , 103 ].…”
Section: The Functional Interplay Between Fgf/fgfr Signaling and Bmentioning
confidence: 99%